2021
DOI: 10.1007/s13555-021-00483-2
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 and Interleukin-23: A Narrative Review of Mechanisms of Action in Psoriasis and Associated Comorbidities

Abstract: Psoriasis is an immune-mediated inflammatory skin disease associated with numerous inflammatory comorbidities, including increased cardiovascular risk. The interleukin (IL)-23/IL-17 axis plays a central role in the immunopathogenesis of psoriasis and related comorbidities by acting to stimulate keratinocyte hyperproliferation and feed-forwarding circuits of perpetual T cell-mediated inflammation. IL-17 plays an important role in the downstream portion of the psoriatic inflammatory cascade. This review discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 143 publications
(101 reference statements)
2
39
0
Order By: Relevance
“…Similarities exist between the immunopathologies of psoriasis, atherosclerosis and metabolic syndrome. This includes promoting the differentiation of Th1 and Th17 cells and the secretion of pro-inflammatory cytokines such as TNF-α, IFN-γ, IL-17A and IL-22 [ 31 ]. In atherosclerosis, IL-17 and TNF-α synergistically activate NF-κB signaling and mitogen-activated protein kinases to induce neutrophil-attracting chemokines and other inflammation modulators, and increase aortic inflammation and thrombosis, eventually exacerbating cardiovascular diseases and increasing the morbidity associated with them [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarities exist between the immunopathologies of psoriasis, atherosclerosis and metabolic syndrome. This includes promoting the differentiation of Th1 and Th17 cells and the secretion of pro-inflammatory cytokines such as TNF-α, IFN-γ, IL-17A and IL-22 [ 31 ]. In atherosclerosis, IL-17 and TNF-α synergistically activate NF-κB signaling and mitogen-activated protein kinases to induce neutrophil-attracting chemokines and other inflammation modulators, and increase aortic inflammation and thrombosis, eventually exacerbating cardiovascular diseases and increasing the morbidity associated with them [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This includes promoting the differentiation of Th1 and Th17 cells and the secretion of pro-inflammatory cytokines such as TNF-α, IFN-γ, IL-17A and IL-22 [31]. In atherosclerosis, IL-17 and TNF-α synergistically activate NF-κB signaling and mitogen-activated protein kinases to induce neutrophil-attracting chemokines and other inflammation modulators, and increase aortic inflammation and thrombosis, eventually exacerbating cardiovascular diseases and increasing the morbidity associated with them [31]. The neutralization of IL-17 lead to a significant improvement in patients with psoriasis or ankylosing spondylitis including lasso cardiovascular comorbidities [32,33] Bertol et al found that the expression of IL-17A in the vascular fraction of the adipose tissue stroma was higher in overweight and obese patients compared to the control group with a normal body weight, contrary to the earlier opinion that IL-17A counteracts adipogenesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is acknowledged that these disorders share a link with chronic inflammation based on the activation of myeloid DCs and endothelial cells, promoting differentiation of Th1 and Th17 cells and secretion of pro-inflammatory cytokines such as TNF-α, IFN-γ, IL-17A, and IL-22, via activation of NF-κB and MAPK signaling [62].…”
Section: Il-17 Isoforms Beyond Psoriasismentioning
confidence: 99%
“…Noteworthy is that it stimulates the proliferation and differentiation of T lymphocytes, Th1, Th17, and Th22, which in turn will produce TNF-α, IL-17, IL-22, favoring initiation of a self-propelled cycle of inflammation. Essentially, this cytokine plays an indirect role in disease pathogenesis by promoting adaptive immune effects of the IL-23/IL-17 axis [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%